Safety of brilliant cresyl blue staining protocols on human granulosa and cumulus cells - Alcoba, Diego Duarte; Conzatti, Maiara; Ferreira, Gustavo Dias; Pimentel, Anita Mylius; Kussler, Ana Paula; Capp, Edison; Corleta, Helena von Eye; Brum, Ilma Simoni (Zygote, 2016)
The selection of human immature oocytes destined for in vitro maturation (IVM) is performed according to their cumulus-oocyte complex (COC) morphology. In animal models, oocyte pre-selection with brilliant cresyl blue (BCB) staining improves fertilization and blastocyst rates and even increases the number of calves born. As the granulosa cells and cumulus cells (GCs and CCs) have a close relationship with the oocyte and are available in in vitro fertilization (IVF) programs, applying BCB staining to these cells may help to elucidate whether BCB shows toxicity to human oocytes and to determine the safest protocol for this dye. GCs and CCs were isolated from 24 patients who underwent controlled ovarian stimulation. After 48 h, cells were exposed to: Dulbecco's Modified Eagle Medium (DMEM) with or without phenol red, DPBS and mDPBS for 60 min; 13, 20 and 26 μM BCB for 60 min; and 60, 90 or 120 min to 13 μM BCB. Cellular viability was tested using 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) and trypan blue assays. The 20 and 26 μM BCB exposures resulted in lower cell viability, similar to when cells were exposed to BCB for 90 or 120 min. GCs and CCs viabilities were equal among control group and 13 μM BCB group after 60 min. BCB staining was not toxic to GCs and CCs when the regime of 13 μM BCB for 60 min was used. Due to the close molecular/biochemical relationship between these cells and the gamete, we propose that it is unlikely that the use of BCB could interfere with the viability/health of human oocytes.